Repeated Exposure to Taekwondo Combat Modulates the Physiological and Hormonal Responses to Subsequent Bouts and Recovery Periods - Bridge, Craig A; Sparks, Andy S; McNaughton, Lars R; Close, Graeme L; Hausen, Matheus; Gurgel, Jonas; Drust, Barry (Journal of strength and conditioning research, 2018)
Bridge, CA, Sparks, SA, McNaughton, LR, Close, GL, Hausen, M, Gurgel, J, and Drust, B. Repeated exposure to taekwondo combat modulates the physiological and hormonal responses to subsequent bouts and recovery periods. J Strength Cond Res XX(X): 000-000, 2018-This study examined the physiological and hormonal responses to successive taekwondo combats using an ecologically valid competition time structure. Ten elite male international taekwondo competitors (age 19 ± 3 years) took part in a simulated championship event. The competitors performed 4 combats that were interspersed with different recovery intervals (63 ± 4, 31 ± 3 and 156 ± 5 minutes, respectively). Heart rate (HR) was measured during the combats and venous blood samples were obtained both before and after each combat to determine the plasma metabolite and hormone concentrations. The plasma noradrenaline (21.8 ± 12.8 vs. 15.0 ± 7.0 nmol·l) and lactate (13.9 ± 4.2 vs. 10.5 ± 3.2 mmol·l) responses were attenuated (p < 0.05) between combat 1 and 4. Higher (p < 0.05) HR responses were evident in the final combat when compared with the earlier combats. Higher (p < 0.05) resting HR (139 ± 10 vs. 127 ± 12 b·min), plasma lactate (3.1 ± 1.2 vs. 2.0 ± 0.7 mmol·l), glycerol (131 ± 83 vs. 56 ± 38 μmol·l) and nonesterified free fatty acid (0.95 ± 0.29 vs. 0.71 ± 0.28 mmol·l) concentrations were measured before combat 3 compared with combat 1. Repeated exposure to taekwondo combat using an ecologically valid time structure modulates the physiological and hormonal responses to subsequent bouts and recovery periods. Strategies designed to assist competitors to effectively manage the metabolic changes associated with the fight schedule and promote recovery between the bouts may be important during championship events.